16 Management of cardiovascular risk in SLE. (1st September 2020) - Urowitz, Murray; Bonfá, Eloisa; Pons-Estel, Bernardo
Abstract : Case 1: 39-year-old female with a premature atherosclerotic event: Murray Urowitz: This case is of historical importance as it initiated the investigations leading to the description of the bimodal mortality program in systemic lupus erythematosus (SLE). MB is a 39-year-old female with a history of SLE diagnosed at 19 years old. Lupus manifestations included arthralgia/arthritis, pericarditis, significant skin involvement with photosensitivity, and malar and discoid rashes. There was no history of nephritis. Extensive skin involvement necessitated daily steroids for many years. Every attempt to taper steroids below 20 mg resulted in significant flares. She was treated with azathioprine, but despite this continued to require steroids to control symptoms over the next 19 years. She presented to the emergency room (ER) for evaluation of retrosternal chest pain. The ER physician thought the likely etiology was pericarditis, and consideration was given to increasing the patient's steroids. However, on physical examination she was found to be hypertensive and electrocardiogram (ECG) showed evidence of an old anterolateral myocardial infarction (MI) and diffuse ST depressions. Cardiac enzymes were elevated. Shortly after being admitted to the hospital, she developed worsening chest pain. Repeat ECG showed worsening ST depressions and acute ST elevations. She rapidly decompensated and died soon thereafter of acute MI. Autopsy revealed cardiomegaly, and generalised atherosclerosis with severe disease of all coronary arteries, mild disease of the aorta, moderate disease of iliac arteries, severe disease of left renal artery, LAD, RCA, LCx occluded by old recanalised thrombi. There was evidence of old anterolateral infarct and new anteroseptal infarct. The pathologist concluded: 'This patient is of interest from many points of view, one of which is the development of such severe atherosclerotic disease at such an early age in a non-diabetic female .' Discussion Point: Premature atherosclerotic events are a major comorbidity in SLE, and early diagnosis and prevention therapy are crucial Case 2: 20-year-old Caucasian female with hypertension: Murray Urowitz: A 20-year-old Caucasian female presented with malar rash, polyarthritis (MCPs, PIPs bilaterally), Raynaud's phenomenon, oral ulcers, and pleurisy. Serology: ANA + (1/1600 IF), anti-DNA (+), normal C3/C4, no cytopenias. There was no evidence of other organ involvement. She was treated with chloroquine 250 mg/day with good response. Two years later she flared with polyarthritis and was treated with prednisone 40 mg/day, gradually decreased to 15 mg/day. Her atherosclerotic risk factors included: BP: 130–139/80–89 mmHg Cholesterol: 220–240 mg/dl (managed with low-fat diet) Triglycerides: 250–350 mg/dl Ex-smoker (quit in 1982, approximately 4–5 pack-years) No diabetes No obesity (BMI=24.2) No family history of premature coronary artery disease Age 24 years: Pregnancy/healthy boy with C-section due to pre-eclampsia. Age 24– 27 years : She had relapsing-remitting disease (mainly mucocutaneous and musculoskeletal): treated with prednisone 15–30 mg/day consistently, Chloroquine 250 mg/day, topical treatments. Azathioprine was added as a steroid-sparing agent but discontinued later due to a hypersensitivity reaction. Age 27 years: She suffered an Acute MI(STEMI) with typical chest pain, ECG changes, plus elevated cardiac enzymes. Angiogram revealed completely occluded right coronary artery, moderate occlusion (approximately 50%) in circumflex and left anterior descending arteries. She received conservative treatment: acetylsalicylic acid 650 mg/day and thiazide diuretics. Age 28 years: This is the first time her hypertension is mentioned in rheumatology clinical notes, consistently 130–140/95–105 mmHg and attributed to glucocorticoids. Diltiazem 90 mg/day was added to her therapy. Age 29 years: She experienced unstable angina, was admitted to Hospital and had a triple bypass. The operation was uneventful. Propranolol 20 mg bid was added. There had been no active disease (clinically and serologically for the last 6 months before the surgery). The patient remained well after the bypass surgery. BP was controlled. Gemfibrozil 600 mg/day was added for cholesterol/triglycerides. Age 30 years : Her second pregnancy with birth of a healthy girl by C-section. She remained clinically/serologically quiescent afterwards and tapered prednisone successfully, discountinuing at age 30 years. Maintenance therapy was chloroquine 250 mg/day. There were no other complications. She died at the age of 50 (cause unknown). Discussion Point: This patient was not clinically hypertensive according to older guidelines. However, she was hypertensive according to the new AHA guidelines of <130/<80 which should become our new standard for diagnosing and treating hypertension in SLE Case 3: Managing cardiovascular risk in a 50-year-old woman diagnosed with SLE 10 years ago: Eloisa Bonfá: A 50-year-old woman diagnosed with SLE 10 years ago, presented with malar rash, polyarthritis, thrombocytopenia, proteinuria, hypertension, normal creatinine, positive anti-dsDNA and low complement. She had been a smoker for 15 years. She was treated with mycophenolate mofetil (MMF) prednisone, hydroxychloroquine (HCQ), anti-hypertensive with complete renal response in 6 months and sustained remission since then. Carotid ultrasound revealed presence of plaques. She had a history of diabetes controlled with metformin and her father had a history of MI. She currently has no complaints or features of lupus. Her BP is 120/80 on MMF (1.0 g/day), HCQ and ACE inhibitor. Her labs are presently normal, except for TC 265 mg/dL; LDL 183 mg/dL; HDL 52 mg/dL; TG150 mg/dL. Discussion Point: What do you consider the most appropriate management for cardiovascular risk for this patient? High-risk patient (target LDL <100 mg/dL): Start on high dose statin and other measures (lifestyle intervention, smoking cessation, diet orientation, blood pressure control and check contraceptive drugs/hormonal replacement therapy) and reduce dose according to LDL levels. High-risk patient (target LDL <70 mg/dL): Start on high dose statin, low dose aspirin (ASA) and other measures and reduce dose according to LDL levels. High-risk patient (target LDL <70 mg/dL): Start on high dose statin and other measures and reduce dose according to LDL levels. High-risk patient (target LDL <70 mg/dL): Start on high dose statin and other measures and sustain dose independent of LDL levels. High-risk patient (target LDL <100 mg/dL). Start on low dose statin and other measures. Adjust statin as necessary. Case 4: Managing cardiovascular risk in a 35-year-old woman diagnosed with SLE 3 years ago: Eloisa Bonfá: A 35-year-old woman diagnosed with SLE 3 years ago, presented with malar rash, polyarthritis, thrombocytopenia, proteinuria, hypertension, normal creatinine, positive anti-dsDNA and low complement. She is a non-smoker. She was treated with MMF, prednisone, HCQ, anti-hypertensive with complete renal response within 6 months and sustained remission since then. She currently has no complaints or features of lupus. Her BMI=24Kg/m2, BP 120/80 on MMF (1.0 g/day) and an ACE inhibitor. She self-discontinued HCQ 1 year ago. Presently her labs are normal, except for TC 168 mg/dL; LDL 120 mg/dL; HDL 30 mg/dL, TG 90 mg/dL. Discussion Point: What do you consider the most appropriate management for cardiovascular risk for this patient? Low-risk patient (target LDL <100 mg/dL): Start on low dose statin and other measures (lifestyle intervention, smoking cessation, diet orientation, blood pressure control and check contraceptive drugs/hormonal replacement therapy). Low-risk patient (target LDL <100 mg/dL): Start on low dose statin, HCQ and other measures. Low-risk patient (target LDL <100 mg/dL): Start on HCQ 3 months and other measures if no improvement, add low-dose statin. Low-risk patient (target LDL <100 mg/dL): Start on HCQ 3 months and other measures. Check for hypothyroidism. If no improvement, add low dose statin. Low risk patient (target LDL <100 mg/dL): No need for specific therapy for dyslipidemia. Lifestyle intervention, smoking cessation, diet orientation, blood pressure control and check contraceptive drugs and hormonal replacement therapy. If no improvement, add low dose statin. Learning Objectives: Describe the present burden of atherosclerotic vascular disease in SLE Explain the occurrence of subclinical and preclinical disease Discuss approaches for better control of risk factors for the future including hypertension and hyperlipidemia Describe possible beneficial effects of antimalarials